The relationship between parental support and learning independence - Asra Aila; Netrawati Netrawati (Consilium, 2021)
This research is motivated by a phenomenon in the field where it is still found that students do not have the courage to express their opinions in front of the class, students often cheat on friends' assignments, go in and out during the learning process, do not do homework assignments, and there are still students who have a dependency on other people in solving them. Homework or problems in studying. One of the factors for the formation of independent learning in students is determined by social sources, namely adults who are in the student's environment such as parents, coaches, family members, and teachers who are able to support student learning activities. This study aims to look at the description of the learning independence of students, the description of parental support, and identify differences in the learning independence of students based on parental support.The type of research used is descriptive correlational. The population of this study was 180 students at SMP N2 Ranah Pesisir, with a sample of 125 students, who were selected using simple random sampling technique. The data collection used a learning independence questionnaire and a parental support questionnaire with a Likert scale model. The data processing with a descriptive approach, the researcher used Microsoft Excel with a simple statistical formula, then for the correlation analysis the researcher used the Pearson correlation product moment formula assisted by using the SPSS version 16.0 program.The results of this study indicate; (1) parental support is in the very high category with a frequency of 65 and a percentage of 52.0%. (2) the learning independence of students is in the high category with a frequency of 72 and a percentage of 57.6%. (3) there is a significant positive relationship between parental support and learning independence with the value of the correlation coefficient between parental support (X) and learning independence (Y) is 0.617 and a significance value of 0.000. Based on the guidelines for the interpretation of the correlation coefficient, with a correlation value of 0.617 it has a strong level of relationship